CRE: A Systematic Method for COTS Components Selection - Alves, Carina; Castro, Jaelson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2001.23989, 2001)
The market interest in developing reliable and stable products at shorter development time and reduced cost, has led to an increasing surge of interest in Component-Based Software Engineering. The success of these systems largely depends on the effective selection of components that meet users requirements. In this context, the products evaluation needs to be a simultaneous process with the requirements acquisition. This paper presents the CRE Method (COTS-Based Requirements Engineering), which is centered on requirements to assist the COTS selection process. The selection of medical packages is used as a case study.